Clinton Joseph Davisson papers - Davisson, Clinton Joseph, 1881-1958.
Correspondence, memoranda, reports, notes, statistics, biographical material, graphs, blueprints, photographs, and other papers pertaining chiefly to Davisson's research while he was employed by Bell Telephone Laboratories, Inc., and Western Electric Company. Documents his study of the secondary emission of electrons, electron optics, the construction of instruments for electron focusing, wave properties of electrons, and crystal physics used to develop quartz crystal plates as circuit elements. Includes lecture notes from the University of Virginia and Davisson (Davison) family correspondence.
Physicist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Davison family -- Correspondence; Bell Telephone Laboratories; University of Virginia; Western Electric Company; Crystallography; Electric circuits; Electron optics; Electrons; Electrons -- Diffraction; Electrons -- Emission; Wave mechanics; Physicists